Numerical Analysis of the Influence of the Modification of the Ladle Shroud on Fluid Flow Behavior in a One-strand Tundish during Continuous Steel Casting - Suchan, Hanna; Cwudziński, Adam (Journal of Casting & Materials Engineering, 2021)
A tundish is a device from which liquid steel is pour into a mold. Therefore tundish hydrodynamic conditions have a significant impact on solidification during continuous steel casting (CSC) process. Modification of ladle shroud workspace, allows for the modification of liquid steel movement in the tundish. In the following work, numerical simulations were performed which allowed the impact of the modification of the ladle shroud workspace on the liquid steel flow structure in a one-strand tundish to be determined. In order to assess the impact of the modification of the ladle shroud on the behavior of the liquid steel in the tundish, simulations were performed, on the basis of which the percentage share of stagnant, ideal mixing and plug flow zones were determined. In addition, the mixing parameters were determined, allowing the estimation of casting duration during sequential casting. The flow fields of liquid steel for each modification of the ladle shroud were performed. The average velocity of liquid steel flowing through the tundish, the Reynolds number and turbulent intensity were also described. The obtained results showed, among others, that the application of three cylinders with a diameter of 0.041 m into the ladle shroud with a diameter of 0.11 m increases the share of active flow in the tundish in relation to the tundish with Conventional Ladle Shroud. At the same time, applying a ladle shroud with a diameter of 0.11 m during casting is the most favorable in relation to the hydrodynamics of the tundish.